IMPLEMENTASI PROGRAM BINA PRIBADI ISLMA DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI SDIT HARAPAN UMMAH KARAWANG - Naina Nurparida; Debidik Nabilatul Fauziah; Neng Ulya (STAI Ihyaul Ulum Gresik, 2026)
Islamic Personal Development is an educational and character building activity in the form of group-based studies that are carried out every week. Coaching is not the same as learning because the goal of coaching is the formation of a superior person, not adding knowledge and skills. By combining the national curriculum and the curriculum created by JSIT itself, especially at SD IT Harapan Ummah Karawang which has a special program oriented towards fostering the character of students, namely the